Reasons for successful clinical outcome following pulmonary vein isolation despite lack of persistent LA‐PV conduction block. Issue 7 (4th June 2019) - Pandozi, Claudio; Lavalle, Carlo; Ficili, Sabina; Russo, Maurizio; Galeazzi, Marco; Rio, Teresa; Centurion Aznaran, Carlos; Malacrida, Maurizio; Colivicchi, Furio
Abstract: The mechanisms of atrial fibrillation (AF) induction and maintenance, including those involved in paroxysmal atrial fibrillation, are not completely known; this limits our ablation strategies and prevents us from understanding what we are actually doing when performing pulmonary vein isolation. In this report, we focus on the commonly used ablation strategies for AF and question the importance of complete pulmonary vein isolation in achieving lasting success in the ablation of AF. We also discuss in detail the absence of durable pulmonary vein isolation in patients without arrhythmic recurrences after AF ablation and the possibility to cure paroxysmal AF without concomitant pulmonary vein isolation, provocatively questioning the dogma of pulmonary vein isolation as the cornerstone of AF ablation. Finally, a prospective personalized approach in the individual patient is advocated.